2020
DOI: 10.1111/jfd.13264
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci (QTL) associated with resistance of rainbow trout Oncorhynchus mykiss against the parasitic ciliate Ichthyophthirius multifiliis

Abstract: The parasitic ciliate Ichthyophthirius multifiliis has a low host specificity eliciting white spot disease (WSD) in a wide range of freshwater fishes worldwide. The parasite multiplies rapidly whereby the infection may reach problematic levels in a host population within a few days. The parasite targets both wild and cultured fish but the huge economic impact of the protozoan is associated with mortality, morbidity and treatment in aquacultural enterprises. We have investigated the potential for genetic select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…We found that the major QTL associated with resistance toward V. anguillarum were clustered on rainbow trout chromosome 21 (Omy 21). It differs from QTL associated with F. psychrophilum resistance on chromosome 19 (Omy19) ( Wiens et al, 2013 ) and toward the parasitic ciliate Ichthyophthirius multifiliis on chromosome 16 and 17 (Omy 16 and 17) ( Jaafar et al, 2020 ) confirming that resistance mechanisms in a specific fish species toward different pathogens differ considerably ( Fraslin et al, 2020 ). In the present work, the favorable homozygote (considering the top SNP) had an overall mortality of 37%, while the opposite homozygote had a mortality of 87%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that the major QTL associated with resistance toward V. anguillarum were clustered on rainbow trout chromosome 21 (Omy 21). It differs from QTL associated with F. psychrophilum resistance on chromosome 19 (Omy19) ( Wiens et al, 2013 ) and toward the parasitic ciliate Ichthyophthirius multifiliis on chromosome 16 and 17 (Omy 16 and 17) ( Jaafar et al, 2020 ) confirming that resistance mechanisms in a specific fish species toward different pathogens differ considerably ( Fraslin et al, 2020 ). In the present work, the favorable homozygote (considering the top SNP) had an overall mortality of 37%, while the opposite homozygote had a mortality of 87%.…”
Section: Discussionmentioning
confidence: 90%
“…This mid-density genotyping array has proven to be of great value for investigating the genetic basis of phenotypic variation and host-pathogen interactions. The applicability of the 57 K SNP array (Affymetrix Axiom ® ) was confirmed for detection of QTL associated with rainbow trout resistance against infectious hematopoietic necrosis virus (IHNV) ( Vallejo et al, 2019 ), columnaris disease ( Silva et al, 2019 ), BCWD ( Vallejo et al, 2017 ; Liu et al, 2018 ), enteric red mouth disease (ERM) ( Zuo et al, 2020 ) and white spot disease (WSD) ( Jaafar et al, 2020 ). Correspondingly, an array developed for Atlantic salmon ( Salmo salar ) was applied to detect QTL associated with resistance in this host species against salmonid alphavirus (SAV) ( Hillestad et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression analysis was performed as pre viously described by Jaafar et al (2020). The gills and fins were homogenized using the Tissue-lyser II (cat.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…For reference genes, ARP, β-actin and elongation factor α (ELF-1α) were applied. Sequence details for primer and probes were used according to Jaafar et al (2020). By using the software NormFinder (Andersen et al 2004), evaluating the applicability of reference genes and combinations of these, an average of the 3 genes were found to be the most suitable as reference.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…QTL for resistance in rainbow trout against Myxobolus cerebralis was studied by Hedrick et al (2003) and later by Baerwald et al (2011). Investigation of singlenucleotide polymorphism (SNP) markers indicated that some genes associated with resistance towards I. multifiliis are located on rainbow trout chromosomes 16 and 17 (Jaafar et al, 2020). Innate response genes in the Atlantic salmon were targeted by Gilbey et al (2006) focusing on gyrodactylid monogeneans (Gyrodactylus salaris).…”
Section: Genetic Control Through Breedingmentioning
confidence: 99%